Caractéristiques d'activités d'évaluation de la compétence langagière à l'université - Martine Peters; Louise Bélair
It generally accepted that superior language skills are an important factor when it comes to succeeding in post-secondary education. Even though it is recognized that superior language skills are important for academic achievement and that most new students do not possess these skills, these are not being taught and are rarely evaluated in undergraduate courses. Most university professors are finding that an increasing number of students have inferior or low level language skills in French language. Our research examines the importance placed on language skills in teacher education programs with the objective of analyzing the characteristics of activities used to evaluate language skills in these programs. Our findings show that there are differences in the evaluation pertaining to the following characteristics : 1) communicative versus linguistic components, 2) formative versus summative evaluations, 3) oral versus written productions, and finally 4) individual versus collaborative evaluations.